Nano Carbon Black And Activated Carbon From Agricultural Waste Filled Epoxy Composites - Firoozian, Parisha (2012)
Carbon blacks and activated carbons derived from agricultural wastes such as bamboo stem (BS), coconut shells (CNS) and oil palm empty fiber bunch (EFB), were obtained by pyrolysis of these natural fibers at 700 0C and subsequently activated with KOH and H3PO4. The various carbon blacks and activated carbons prepared were characterized and used as filler in epoxy composites. The physical and chemical properties of the carbon blacks and activated carbons were studied using thermogravimetric analyzer (TGA), scanning electron microscope (SEM), transmission electron microscopy (TEM), fourier transform infrared (FT-IR) and X-ray diffraction (XRD) of activated carbons and carbon black were also carried out. The effect of pyrolysis on carbon black and two different chemical activations by H3PO4 and KOH on activated carbons were also studied. It was observed that KOH activation proved more effective than H3PO4 and physical activation on agricultural wastes resulted in higher percentage of mesopores and higher surface area.